2014
DOI: 10.1016/j.socscimed.2014.09.040
|View full text |Cite
|
Sign up to set email alerts
|

Life events trajectories, allostatic load, and the moderating role of age at arrival from Puerto Rico to the US mainland

Abstract: Our aim was to examine the effects of trajectories of stressful life events on allostatic load, measured over a two year time period, and to investigate the roles of language acculturation and age at migration in this association, in a sample of Puerto Rican migrants. We used data from the Boston Puerto Rican Health Study; a population-based prospective cohort of older Puerto Ricans recruited between the ages of 45 and 75 years. The Institutional Review Boards at Tufts Medical Center and Northeastern Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 73 publications
(112 reference statements)
0
19
0
Order By: Relevance
“…It is possible allostatic load accumulates too gradually for the stress of teenage alcohol consumption to significantly impact ALI measures during teenage years. However, as previously mentioned, adults do not exhibit positive relationships between allostatic load and alcohol consumption either and, in some samples, the association is negative (Ar evalo et al, 2014;Kusano et al, 2016;McClure et al, 2015;Petrovic et al, 2016).…”
Section: Allostatic Load During Growth a N D De V E L O P Me N Tmentioning
confidence: 82%
See 4 more Smart Citations
“…It is possible allostatic load accumulates too gradually for the stress of teenage alcohol consumption to significantly impact ALI measures during teenage years. However, as previously mentioned, adults do not exhibit positive relationships between allostatic load and alcohol consumption either and, in some samples, the association is negative (Ar evalo et al, 2014;Kusano et al, 2016;McClure et al, 2015;Petrovic et al, 2016).…”
Section: Allostatic Load During Growth a N D De V E L O P Me N Tmentioning
confidence: 82%
“…In other research, medications were accounted for by adjusting the construction of the reported ALI. For example, some researchers add a point for every biomarker directly affected by a medication to the ALI regardless of the biomarker's current level, although specific adjustments vary by study (Ar evalo, Tucker, & Falc on, 2014;Doamekpor & Dinwiddie, 2015;Gale, Booth, Starr, & Deary, 2015;Hampson et al, 2009;Mattei et al, 2010;Robertson et al, 2014;Robertson & Watts, 2016 Clinically based constructs directly counteract the usefulness of ALIs to determine individuals in a group at greatest underlying risk for future health issues and early mortality. However, within medical settings, applying ALIs using clinical cut-points may be more practical, particularly as sample distributions are not usually available when working with individual patients (Mauss et al, 2016).…”
Section: Methods Studiesmentioning
confidence: 99%
See 3 more Smart Citations